ADSORPTION OF ACID ORANGE-10 DYE ONTO CERIUM DIOXIDE NANOPARTICLES: A KINETIC STUDY - Zuas, Oman -; Budiman, Harry; Nuryantini, - (LIPI Press, 2015)
In this paper, a preserve work on the ability of cerium dioxide nanoparticles (CeO2-NPs) to remove acid orange-10 (AO-10) dye from aqueous solution by adsorption, focusing on the study of the kinetic of AO-10 dye adsorption onto CeO2-NPs surface, was reported. The kinetic data obtained at different concentration of AO-10 dye were analyzed using three different kinetic models, including pseudo-first order, pseudo-second order, and Elovich model. The result showed that the kinetic data fitted with the pseudo-second order kinetic model. Based on the adsorption mechanism data obtained through intraparticle diffusion evaluation, it was found that the adsorption of AO-10 dye onto CeO2-NPs was controlled by the mass transfer rate of the adsorbate molecule from outer to innerof the adsorbent particle. Thus, considering both previous and present studies, it can be suggested that the CeO2-NP appears to be a good adsorbent for the removal of AO-10 dye from aqueous solutions.